Inherited risk? A scoping review on gambling in family history - Nadya Putri Cahyani Bahar; Citra Wahyuni; Mohammad Nursalim Malay (Jurnal Psikologi Tabularasa, 2025)
The scoping review examines the influence of family gambling history on the development of gambling disorders through psychological, social, and environmental mechanism. Findings indicate that individuals with a family history of gambling are more likely to develop maladaptive cognitive schemas, increased impulsivity, and ineffective coping strategies, reinforcing addictive behaviors. Family dysfunction, unresolved trauma, and social stigma further contribute to risk factors. Integrating psychological and family-based interventions, such as cognitive restructuring and family therapy, is essential for breaking the cycle of gambling addiction. Future research should explore the interplay of genetic, psychological, and social factors to develop more targeted prevention and intervention strategies.